Imatinib as a paradigm of targeted cancer therapies - Druker, Brian (Henry Stewart Talks, 2007)
Clinical description of chronic myeloid leukemia (CML), Molecular pathogenesis of CML, The BCR-ABL tyrosine kinase as a therapeutic target, Preclinical and clinical development of the ABL tyrosine kinase inhibitor, imatinib, Mechanisms of resistance to imatinib, Development of novel ABL tyrosine kinase inhibitors for imatinib-resistant CML, Imatinib and gastrointestinal stromal tumor, Extending the imatinib paradigm, Lessons learned from the clinical trials of imatinib
Archived at 2018/05/31